EKONOMI POLITIK PEMBANGUNAN INFRASTRUKTUR DAN KEPENTINGAN KAPITAL - Ridha, Muhammad (JPP (Jurnal Politik Profetik), 2016)
This research is a descriptive political economy on what and who obtains the most advantages of the politics of building infrastructure and of creating local, regional and international financial schemes. For its analysis, the writer applies common logic of Karl Marx on creating values in production of capitalism facilitated by the distribution process of creating highways and other infrastructures, which is commonly known as a process of producing spaces. Through observation, it is found that the process of infrastructure politics, in fact, provides more benefits to local, national and global economic oligarchy, than to the publics in general.